The application of fecal coliform - fecal streptococci ratios as indicators of enteric pollution in Pammel Creek - Olson, Harlan (My University, 1973)
This study of Pammel Creek, La Crosse County, Wisconsin, was initiated in order to quantitatively assess the degree, the type, and the specific sources of enteric pollution in the stream. Fecal coliforms and fecal streptococci were selected as the indicator organisms. Both types of bacteria are present consistently in the feces of all warm-blooded animals. Rainfall and the resulting storm water run-off probably contributed to the enteric pollution of Pammel Creek in two ways: by loading the stream with bacteria and nutrients, and by saturating the soil around septic system drainfields. Fecal coliform tests of July and August, 1971, revealed high levels of enteric pollution at all test stations. Only 3 of 58 samples yielded results which were under the suggested standard of 200 fecal coliforms per 100 ml for primary contact recreation. The fecal coliform - fecal streptococci ratios obtained in the test series of 1972 and 1973, indicated a probable injection point for human fecal contaminants in the vicinity of Station 12. Out of a total of 32 test samples from Station 12 and its subdivisions, 75% gave ratios which indicated enteric pollution which was predominantly of human origin. Ratios obtained at the other sampling sites suggested enteric pollution derived from warm-blooded animals other than man. In view of these-results, it is recommended: (1) that measures be taken to immediately correct defects in the septic sewage facilities in the vicinity of Station 12; (2) that priority be given to the extension of sewage lines connecting the municipal sewage system of the city of La Crosse with the residential areas in State Road Coulee and adjacent coulees; (3) that measures be taken to control run-off from concentrations of fecal contaminants on farms located on the Pammel Creek watershed; and (4) that thorough studies be made concerning the impact of any new development which affects the quality of water in Pammel Creek.
Keywords: Sewage disposal in rivers, lakes, etc. -- Wisconsin -- Pammel Creek (La Crosse County); Pammel Creek (La Crosse County, Wis.)